(+)-Borneol attenuates oxaliplatin-induced neuropathic hyperalgesia in mice. Issue 3 (10th February 2016) - Zhou, Hai-Hui; Zhang, Li; Zhou, Qi-Gang; Fang, Yun; Ge, Wei-Hong
Abstract : Common chemotherapeutic agents such as oxaliplatin often cause neuropathic pain during cancer treatment in patients. Such neuropathic pain is difficult to treat and responds poorly to common analgesics, which represents a clinical challenge. (+)-Borneol, a bicyclic monoterpene present in the essential oil of plants, is used for analgesia and anesthesia in traditional Chinese medicine. Although borneol has an antinociceptive effect on acute pain models, little is known about its effect on chemotherapy-induced neuropathic pain and its mechanism. We found that (+)-borneol exerted remarkable antihyperalgesic effects in a mouse model of oxaliplatin-induced neuropathic pain. In addition, (+)-borneol blocked the action of the transient receptor potential ankyrin 1 agonist in mechanical and cold stimulus tests. Repeated treatment with (+)-borneol did not lead to the development of antinociceptive tolerance and did not affect body weight and locomotor activity. (+)-Borneol showed robust analgesic efficacy in mice with neuropathic pain by blocking transient receptor potential ankyrin 1 in the spinal cord and may be a useful analgesic in the management of neuropathic pain.